Diazepam Reduces Escape and Increases Closed-Arms Exploration in Gerbils After 5 min in the Elevated Plus-Maze - Rico, Javier Leonardo; Muñoz-Tabares, Luisa Fernanda; Lamprea, Marisol R.; Hurtado-Parrado, Camilo (Frontiers in Psychology, 2019)
Despite the wide implementation of the elevated plus-maze (EPM) test to assess anxiety-related behaviors in rodents, the interpretation of these measures in gerbils has received limited attention. Here, male gerbils were treated with vehicle or diazepam, followed by a 20-min EPM session. EPM data were subjected to minute-by-minute, 5-min bins and factor analyses. During the first 5-min, gerbils avoided the closed-arms in favor of the open-arms and diazepam increased open-arms entries; furthermore, a single factor (escape response) explained all the analyzed measures. Only after 5-min, gerbils reduced open-arms exploration and three independent factors emerged for each subsequent 5-min bin. These findings suggest that EPM data from gerbils should be analyzed in at least two 5-min bins. Measures from the standard 5-min session seem to be related to an escape response from the EPM through the open-arms. Once habituated, measures from the second 5-min bin seem to be related to a conflictive situation: keep trying to escape unsuccessfully (due to open-arms height) or seek protection in the closed-arms (unsafe places). Diazepam seems to reduce this conflict by mitigating the escape response (Factor 1 - Anxiety) and increasing closed-arms approach (Factor 2) and risk-assessment (Factor 3). Unlike mice and rats, a decrease in open-arms exploration and an increase in risk-assessment could be interpreted as an anxiolytic-like effect in gerbils.